The Negotiations of a Tax Agreement between Switzerland and Germany - Misha Nagelmackers-Voinov (Graduate Institute Publications, 2014)
This ePaper analyses the negotiations of an agreement on tax cooperation between Switzerland and Germany in 2012. The paper looks at the importance of the balance of power and reveals how domestic constraints and a shrinking win-set can affect double-level negotiations. It also offers an illustration of how governments can shape domestic politics by using international debates while still facing conflicting interests along the increasingly blurred line of domestic and international interests....